2019
DOI: 10.1002/smll.201805435
|View full text |Cite
|
Sign up to set email alerts
|

Environmentally‐Friendly Exfoliate and Active Site Self‐Assembly: Thin 2D/2D Heterostructure Amorphous Nickel–Iron Alloy on 2D Materials for Efficient Oxygen Evolution Reaction

Abstract: A class of 2D layered materials exhibits substantial potential for high‐performance electrocatalysts due to high specific surface area, tunable electronic properties, and open 2D channels for fast ion transport. However, liquid‐phase exfoliation always utilizes organic solvents that are harmful to the environment, and the active sites are limited to edge sites. Here, an environmentally friendly exfoliator in aqueous solution is presented without utilizing any toxic or hazardous substance and active site self‐a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 48 publications
0
41
0
Order By: Relevance
“…Lately, many researchers have tried to develop TMDs as stable and highly active OER catalysts for overall water splitting. [ 22–39 ] To impart such bifunctional catalytic activity, first transition metals such as Co and Ni are frequently incorporated in various approaches, including doping in the ionic form. Yet, there have been only a few studies on the bifunctional catalytic activity of the 1T (or 1T′) phase MoS 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Lately, many researchers have tried to develop TMDs as stable and highly active OER catalysts for overall water splitting. [ 22–39 ] To impart such bifunctional catalytic activity, first transition metals such as Co and Ni are frequently incorporated in various approaches, including doping in the ionic form. Yet, there have been only a few studies on the bifunctional catalytic activity of the 1T (or 1T′) phase MoS 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical calculations demonstrated that the presence of NiFe increases the stability of MoS2. Specifically, by constructing the adsorption diagram, the binding energy of the Ni atom in the plane was found to be larger [201]. Yang et al [202] reported that nickel foam can not only act as a carrier, but also provide a source of Ni (Figs.…”
Section: (A)-(d))mentioning
confidence: 99%
“…For example, Gao and co‐workers fabricated highly disordered amorphous NiFe/2D‐material (Ti 3 C 2 MXene, graphene, and MoS 2 ) heteronanosheets, which exhibited an excellent electrocatalytic performance toward the OER in alkaline media. [ 180 ] The extraordinary electrocatalytic characteristics of the NiFe/MoS 2 sheet heterostructure can be attributed to the following factors: 1) a strong interfacial coupling that contributes to fast electron transfer, 2) the nanoconfinement effect that suppresses the aggregation of active‐site NiFe nanosheets and uniformly exposes the active sites, and 3) synergism between the in situ generated gas and the ultrasonic, which solves the problem of weak van der Waals interactions between the two lamellar structures and favors the assembly of thin metal/MoS 2 ‐heterostructured hybrid nanosheets. DFT calculations further confirmed the experimental results.…”
Section: Advanced Nife‐based Electrocatalystsmentioning
confidence: 99%